Professional Development on the Science of Learning and teachers' Performative Thinking—A Pilot Study. Issue 3 (19th July 2020) - A. Howard‐Jones, Paul; Jay, Tim; Galeano, Laura
ABSTRACT: This pilot study investigated how a brief professional development session on the science of learning impacted teachers' attributions of usefulness to both scientific and performative concepts about teaching. Ratings were collected from teachers attending five events across the United Kingdom ( N = 585) before and after receiving a 90‐min training session. Initial ratings of scientific concepts were positively correlated with age, while initial ratings of performative concepts were negatively correlated with years of experience. Immediately following professional development, the value teachers attributed to scientific concepts for understanding their practice increased, while their valuing of performative concepts decreased. A follow‐up study with a subsample ( N = 153) revealed the impact was reduced but persisted 6–12 weeks later. Results are discussed in terms of the potential for a scientific understanding of learning to empower educators as expert professionals. Abstract : Lay abstract: We asked teachers to rate the usefulness of scientific concepts about learning and statements about teaching that were "performative"‐ i.e. encouraging "teacher‐like" behaviours but offering little insight into learning. Initial ratings of scientific concepts were positively associated with age, with performative statements negatively associated with experience. A 90‐minute training session on the science of learning produced change in directions associated with age and experience, supporting the value of such training for teacher education and development.